UPAYA MENINGKATKAN HASIL BELAJAR GERAK DASAR LARI MELALUI PERMAINAN BOLA WARNA PADA SISWA KELAS II SD NEGERI GETAS 1 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose  of   this study  to  determine the  i mprovement of   learning  outcomes run  the basi c  mot i on  using colorball   game on  t he second  grade students of  SD Negeri 1 District   Wonosalam  Brittle  Demak regency.Impl ementat ion  of   classroom  action  research  was  conducted  in  two  cycles  where  each  cycl e  consists  of   f ourstages:  planning,  action,  observation  (observation),  and  reflection.  Methods  of  data  coll ect ion  in  t his  studyusing  t he  methods  of   document ation,  observat ion,  and  quest ionnaires.  Analysis  of   research  data  wi t hdescript ive anal ysis percentage. Based on the survey  result s  revealed that  t he learning  outcomes of basic motionrun in cycle 1 in the cat egory at  72.72% complete and on cycle 2 increased to 95.45%, the activity of  st udents incycl e 1  of 83  (very good), whil e in t he  second cycle of 92  (very good), the value  of   the average  st udent  in cycl e 1was  79.8 and  in  cycl e  2  was 81.2.  Overall  value obtained  for  each aspect  has  increased.  The  concl usi on  of   thestudy is  t hrough color ball   games  can  improve learning outcomes  run  t he basic  motion.